2009
DOI: 10.1007/s11999-008-0447-5
|View full text |Cite
|
Sign up to set email alerts
|

The Condylar Cutoff Sign: Quantifying Lateral Femoral Condylar Hypoplasia in a Complete Discoid Meniscus

Abstract: We describe the condylar cutoff sign, a radiographic sign in knees with a discoid lateral meniscus, for diagnosis of complete discoid meniscus. We retrospectively reviewed tunnel-view radiographs of 100 patients (100) knees including 50 with complete discoid lateral meniscus and 50 with normal menisci. All patients were 18 years of age or older. All of the knees were arthroscopically examined. We developed a method to measure the prominence of the femoral condyle adjacent to the intercondylar notch on a tunnel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 17 publications
3
45
1
1
Order By: Relevance
“…Numerous studies have outlined the morphological characteristics of DLM [7,[21][22][23][24][25] and, compared with a normal meniscus, patients with DLM have a higher frequency of meniscal tears [5,6]. In this study, we showed that most patients with DLM have a horizontal-type PTFJ.…”
Section: Discussionsupporting
confidence: 53%
“…Numerous studies have outlined the morphological characteristics of DLM [7,[21][22][23][24][25] and, compared with a normal meniscus, patients with DLM have a higher frequency of meniscal tears [5,6]. In this study, we showed that most patients with DLM have a horizontal-type PTFJ.…”
Section: Discussionsupporting
confidence: 53%
“…There has also been recent report of a significant difference in the condylar cut-off sign, which is a plain radiographic finding, between CDLM knees and normal knees [15]. However, the technique used in this report is not particularly convenient as the imaging method differs from normal frontal knee radiography.…”
Section: Introductionmentioning
confidence: 81%
“…Radiographs do not play a significant role in diagnosis [3], in our series we didn't see so called the condylar cutoff sign with the lateral space widening, hypoplasia of the lateral femoral condyle and the lateral tibial spine [10]. MRI can accurately show a discoid meniscus.…”
Section: Discussionmentioning
confidence: 66%
“…Zdjęcia rentgenowskie nie odgrywają istotnej roli w diagnostyce łąkotki tarczowatej [3], w naszej serii nie widzieliśmy poszerzenia przestrzeni przedziału bocznego kolana, ani niedorozwoju kłykcia bocznego kości udowej i wyniosłości międzykłykciowej kości piszczelowej [10]. Rezonans magnetyczny pozwala na najlepsze obrazowanie łąkotki tarczowatej, swoistość tego badania waha się pomiędzy 92-99% [3].…”
Section: Discussionunclassified